2020
DOI: 10.1071/wf18123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of post-wildfire erosion risk and effects on water quality in south-western Australia

Abstract: Investigations of wildfire impact on water resources have escalated globally over the last decade owing to an awareness of climate-related vulnerabilities. Within Australia, research into post-wildfire erosion has focused on water supply catchments in the south-eastern region. Here, we examine post-wildfire erosion risk and its potential for water quality impacts in a catchment in south-western Australia. The catchment of the Harvey River, which drains from forested escarpments onto an agricultural coastal pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The estimated postfire soil erosion rates range from 11‐27 t h −1 y −1 (Table S1), reflecting an increase of over 200%. The absolute values and relative changes are consistent with field measurements from severely burned catchments in NSW (Atkinson, 2012; Blake et al., 2020; Shakesby & Doerr, 2006). The increases in estimated soil erosion in the three tributaries range from 88% in the Gloucester catchment to 358% in the Nowendoc catchment (Figure S3 and Table S1).…”
Section: Subsequent Effects: Floods Soil Erosion and Water Qualitysupporting
confidence: 82%
See 1 more Smart Citation
“…The estimated postfire soil erosion rates range from 11‐27 t h −1 y −1 (Table S1), reflecting an increase of over 200%. The absolute values and relative changes are consistent with field measurements from severely burned catchments in NSW (Atkinson, 2012; Blake et al., 2020; Shakesby & Doerr, 2006). The increases in estimated soil erosion in the three tributaries range from 88% in the Gloucester catchment to 358% in the Nowendoc catchment (Figure S3 and Table S1).…”
Section: Subsequent Effects: Floods Soil Erosion and Water Qualitysupporting
confidence: 82%
“…We apply the RUSLE model (Kinnel, 2010;Renard et al, 1991) to estimate first order the pre and postfire soil erosion rates within the Manning River catchment based on rainfall erosivity, soil erodibility, steepness, land cover and management, using input parameters from preexisting datasets (Yang et al, 2015(Yang et al, , 2018 (see supplements). The dNBR burn severity is included by adjusting the postfire land cover-factor accordingly (Blake et al, 2020;Larsen & MacDonald, 2007) based on satellite data from February 2019 and 2020. The estimated postfire soil erosion rates range from 11-27 t h −1 y −1 (Table S1), reflecting an increase of over 200%.…”
Section: Subsequent Effects: Floods Soil Erosion and Water Qualitymentioning
confidence: 99%
“…First, the linked fire and erosion model system (Figure 1) is subject to multiple data, model, and model linkage uncertainties that have potential for prediction error as discussed extensively in previous publications [24,25]. Recent work has shown that water quality at the basin scale is sometimes minimally impacted despite modeled increases in hillslope erosion [82], emphasizing the need to test and refine erosion and sediment transport models with empirical observations at multiple scales [83]. Most of our predicted first-year post-fire hillslope erosion yields for the 2-year and 10-year rainfall erosivity scenarios (Table 2) are close to the study-wide means of 9.5-22.2 Mg ha −1 and the range of individual hillslope observations of 0.1-38.2 Mg ha −1 from previous fires in the region exposed to moderate rainfall [11,17,47,84].…”
Section: Discussionmentioning
confidence: 99%
“…Research reveals that anthropogenic factors [4,5] and climate change [6][7][8] play a critical role in the frequency of wildfre occurrence and increase in afected areas. Wildfres are not only responsible for the mass destruction of forests but they also have several adverse efects on the natural environment, such as increased erosion risk [9][10][11][12], poor water quality [9], changes in land use [13], and elimination of wildlife [14]. Nevertheless, many Mediterranean plant species have evolved some form of adaptation mechanism for survival in a fre [15].…”
Section: Introductionmentioning
confidence: 99%